Motifs, placements and influences of woodcarving in Muar traditional Malay houses - Yusof, Hanita; Ibrahim, Fawazul Khair; Raja Shahminan, Raja Nafida
Almost every country, race or culture has its own traditional heritage including Malaysia and every state in it. Woodcarving is one of the Malaysian traditional heritage that has been passed through generations and should be preserved and maintained. Unfortunately, it is being forgotten due to the rapid urbanization and led to it getting destroyed and extinct. Nevertheless, there are still many traditional houses in some places which own very interesting woodcarvings that must be studied and analyzed before this heritage is permanently vanished such as in Muar, Johor where it owns an interesting history, thus making it among the earliest inhabited district and rich in woodcarvings. This study aimed to identify motifs and placements of the woodcarvings in traditional Malay houses in the districts of Muar including the influence on it. The research methodologies taken were case studies of existing traditional Malay houses in Muar. Site visits to the chosen houses are carried out where the process of taking data, photography and interviewing the resident as well as additional information from Center of Built Environment in the Malay World (KALAM) at Universiti Teknologi Malaysia (UTM) was then triangulated with the analytic interpretation of local woodcarvers. The results showed the existence of significant motif, placement and very strong influence on the woodcarvings found in these Malay traditional houses in Muar.